2007
DOI: 10.1016/j.jbiomech.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of side impact: Injury criteria, aging occupants, and airbag technology

Abstract: This paper presents a survey of side impact trauma-related biomedical investigations with specific reference to certain aspects of epidemiology relating to the growing elderly population, improvements in technology such as side airbags geared toward occupant safety, and development of injury criteria. The first part is devoted to the involvement of the elderly by identifying variables contributing to injury including impact severity, human factors, and national and international field data. This is followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 95 publications
0
26
0
2
Order By: Relevance
“…Traditional approaches to quantify responses of the human body to impacts have typically included full scale experimental testing involving the use of a post mortem human subject (PMHS) [14]. However, such tests are expensive and time consuming which has lead to the increasing use of numerical modelling [6], for which detailed material models of bone are required.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional approaches to quantify responses of the human body to impacts have typically included full scale experimental testing involving the use of a post mortem human subject (PMHS) [14]. However, such tests are expensive and time consuming which has lead to the increasing use of numerical modelling [6], for which detailed material models of bone are required.…”
Section: Introductionmentioning
confidence: 99%
“…In automotive crashes, impact loading is generally horizontal, i.e., the vector lies along a clock direction: twelve, three or nine and six o'clock representing frontal, side and rear impacts (Backaitis and Mertz, 1994;Kuppa et al, 2003;Morgan et al, 1994;Yoganandan et al, 2014a;Yoganandan et al, 2015a;Yoganandan and Pintar, 2000). Devices such as acceleration and deceleration sleds have been used for over fifty years to simulate such loadings by positioning physical and biological models on their platforms to apply the intended load vector (Maltese et al, 2002;Philippens et al, 2000;Pintar et al, 1997;Yoganandan et al, 2007). The use of a pendulum is another example.…”
Section: Introductionmentioning
confidence: 99%
“…Nearside occupants are at particular risk due to intrusion of the occupant compartment by the impacting vehicle. 56 It has also been found that pulmonary contusions are more likely to occur in lateral impact crashes. 13 While safety features such as side airbags are becoming more common in vehicles, the occupants of side impacts are still in need of better protection.…”
Section: Introductionmentioning
confidence: 99%